2015
DOI: 10.1111/nin.12118
|View full text |Cite
|
Sign up to set email alerts
|

Actor‐Network Theory as a sociotechnical lens to explore the relationship of nurses and technology in practice: methodological considerations for nursing research

Abstract: Actor-Network Theory is a research lens that has gained popularity in the nursing and health sciences domains. The perspective allows a researcher to describe the interaction of actors (both human and non-human) within networked sociomaterial contexts, including complex practice environments where nurses and health technology operate. This study will describe Actor-Network Theory and provide methodological considerations for researchers who are interested in using this sociotechnical lens within nursing and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…; how do social and material elements structure simulation practices, particularly the debrief [ 9 , 10 ]? ; and, how do health technologies impact nursing practice in clinical contexts [ 11 ]?…”
Section: Introductionmentioning
confidence: 99%
“…; how do social and material elements structure simulation practices, particularly the debrief [ 9 , 10 ]? ; and, how do health technologies impact nursing practice in clinical contexts [ 11 ]?…”
Section: Introductionmentioning
confidence: 99%
“…One needs to think in terms of sociotechnical relations as a network of human or nonhuman actors, at a given time and place (5) . In order to understand these sociotechnical relations, which underlie the e-SUS AB strategy, the Actor-Network Theory (ANT) is presented as an appropriate theoretical referential (6) -also applicable in the context of health and nursing (7) .…”
Section: Introductionmentioning
confidence: 99%
“…In the complex practice environment where the nurses and their health technologies operate, the Actor-Network Theory has emerged as a relevant and noteworthy theoretical-methodological framework. 2 Characterized as a branch that challenges the traditional approaches of Sociology, the ActorNetwork Theory, also known as the Sociology of Associations and the Sociology of the Social, originates in the studies of Science, Technology and Society, in which the knowledge production dynamics are investigated, considering human and non-human actors. Developed as from the 1970's, the precursors are Michel Callon, John Law and Bruno Latour, a group of sociologists associated with the Center for the Sociology of Innovation in Paris.…”
Section: Introductionmentioning
confidence: 99%
“…8 This enhances the need for a research approach that provides an understanding of the sociotechnical complexity of this evolution, where no distinction is made among technical, political and social issues. 2 Motivated by the principles of symmetry, hybridization and translation, and due to its theoretical and methodological framework for the study of scientific discoveries and technological innovations, ANT has recently aroused international interest in different knowledge areas, particularly: education, information technologies, administration, sociology, history, planning, geography, environmental studies, information science, public health and nursing. 2,[9][10] In Brazil, we identified that studies related to ANT have focused on the field of digital inclusion, geoprocessing, industrial policy of informatics and innovation, financial system, information systems in health and electronic government.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation